Hyperreactio luteinalis mimicking malignancy during pregnancy with elevated CA-125 - Cheng-Wei Wang; Wei-Min Liu; Ching-Hui Chen (Elsevier, 2019)
Objective: To report a case with benign bilateral ovarian tumor during pregnancy mimicking malignancy. Case report: A 32-year-old women at 20 weeks gestation with large bilateral adnexal masses found on prenatal ultrasound. The cysts had been growing gradually over the course of the pregnancy. MRI show huge multiple cysts in both ovaries. CA-125 was elevated at 260 U/mL. Due to initial impression was malignancy, an excisional surgery was done. Pathology revealed multiple luteinized granulosa cells with benign nature. Conclusion: Hyperreactio luteinalis (HL) is often asymptomatic and discovered incidentally on ultrasound or at the time of cesarean section. As the lesions are self-resolving, management is conservative and surgical intervention is required only in cases with severe complications. HL can be mistaken for malignancy, especially in cases in which the tumor marker CA-125 is elevated, leading to inadvertent surgery. Keywords: Hyperreactio luteinalis, Ovarian tumor, Pregnancy, Ultrasound diagnosis